Answer:
The given expression is simplified as [tex](x + 9)(x -9) = x^{2} - 81[/tex]
Step-by-step explanation:
Here,the given expression is (x+9)(x -9)
Using the ALGEBRAIC IDENTITY:
[tex](a +b)(a -b) = a^2 - b^2[/tex]
Now, here in the given expression (x + 9)(x -9)
Comparing it the left side of the identity,
we get a = x
and b = 9
The right side of the equation is [tex]a^{2} - b^{2}[/tex]
Substituting the value of a and b, we get
⇒ [tex](x + 9)(x -9) = (x)^{2} - (9)^{2}[/tex]
= [tex]x^{2} - 81[/tex]
Hence, the given expression is simplified as [tex](x + 9)(x -9) = x^{2} - 81[/tex]